Pengaruh Job Description, Kompensasi dan Lingkungan Kerja Non Fisik terhadap Motivasi Kerja Pegawai Puskesmas Loa Janan Kabupaten Kutai Kartanegara - Rindha Mareta Kusumawati; I Putu Sukra; Mia Helida; Kartina Wulandari; Apriyani Apriyani (Jurnal Kesehatan Komunitas, 2022)
Lack of human resources is one of the reasons why most employees at Loa Janan Health Center. have double jobs. This study aims to determine: 1. the effect of the job description on the motivation of employees, 2. the effect of compensation on the motivation of employees, 3. the effect of non-physical work environment on the motivation of employees in Loa Janan Health Center. This type of research was quantitative with a Causal approach. The sample consisted of 53 employees. The questionnaire is used to collect the data in this research. The data analysis technique is multiple linear regression analysis, the t-test and predictor contributions are used to test the hypothesis in this research. The results showed that job description has an effect on employee motivation with a contribution of 13.1% influence, it is concluded that the hypothesis is accepted compensation and  Non-physical work environment has no effect on employee motivation with an influence contribution of 0.73% and 5%, it is concluded that the hypothesis is rejected. The conclusions of the research is just job Description has an effect on employee work motivation.. The suggestion of this research are hopefully, the distribution of Job Descriptions is based on the interests and competencies. Besides, adding more human resources to fill job vacancies is necessary to do so that there are no more double jobs in Loa Janan Health Center